First report of inventory and role of macroinvertebrates and fish in Cautín river (38° S, Araucania region Chile) - Vega,R. (2020)
Abstract The Cautin river is located in the 137 years old Araucania region, Chile (38°S), and is characterized by alterations through human interference due agriculture and towns in its surrounding basin, the presence of salmonids, and by its mixed regime, originated from snow melting in summer and rains in winter. The aim of the present study was to make a review of the inventory and ecological role of the benthic inland water macroinvertebrates of the River Cautin, in order to understand their importance in the ecosystem of the river. The fauna of this river includes a fauna composed of endemic and introduced fish, which has, however, been only poorly studied until now. The literature revealed the presence of abundant populations of Diptera, Trichoptera and Ephemeroptera larval stages, and few crustaceans specifically amphipods and freshwater crabs along the river’s course. Many of these macroinvertebrates are prey for both introduced salmonids and native fishes. Similar results have been reported for other southern Argentinean and Chilean Patagonian rivers.